The Urgency of Preserving Regional Languages through Local Educational Curriculum - Pamungkas, Susandi Decapriu Putra; Suputra, Gede Ngurah Darma; Fadillah, Dyah Ajeng Puspa; Rista, Mirsya Lila Agua; Arisandi, Sadira Ramadhani (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2023)
The use of local languages in the era of globalization is currently experiencing a decline. Based on field data, the utilization of local languages through local content education is minimally implemented by educational institutions. This poses a problematic situation as the use of local languages through local content education may vanish and erode due to the advancement of a more globalized world. In the Curriculum 13 itself, the use of local languages in educational institutions is mandated to be included as part of the local content subjects. However, in the